(untitled) (Research, Society and Development, 2022)
The present work proposed to discuss the issue of violence against women in Brazil in the pandemic period. Its general objective was to discuss violence against women in a pandemic context. As specific objectives: Debate on the problem of femicide; Survey the rates of femicide in Brazil during the pandemic period; to point out the main actions to combat femicide, according to the researched works. This work presents a bibliographic survey through reading and analysis of authors who discuss the topic. To obtain data, books, articles, course conclusion works, as well as published magazines and periodicals, as well as statistical data related to the topic published in the pandemic period were consulted. Therefore, the results indicate that Brazil experienced an epidemic of femicides within the coronavirus pandemic, according to official data from the state security secretariats, there was an increase of 22% in femicide cases in 12 states in the first months of the pandemic. (March to April 2020), months of greater social isolation due to the virus. Also, according to the data released, the state that presented the highest rate of femicide was Acre with an increase of 300%, Maranhão also had an increase of 166.7%, the cases went from 6 to 16 in the mentioned period, Mato Grosso had a 150% increase, jumping from 5 to 15 cases. Considering the beginning of the COVID-19 pandemic in March 2020 until December 2021 (according to available data), 2,451 women were victims of femicide in the period, according to the Brazilian Public Security Forum.